2018
DOI: 10.1093/icesjms/fsy048
|View full text |Cite
|
Sign up to set email alerts
|

Investigating fish behavioural responses to LED lights in trawls and potential applications for bycatch reduction in the Nephrops-directed fishery

Abstract: Light-emitting diodes (LEDs) have been tested in trawl fisheries to reduce the bycatch of unwanted species through behavioural stimulation. Previous studies used LED lights to either highlight escaping routes or increase the contact rate with square-mesh panels. However, phototactic responses (moving towards or away from light sources) to LED lights could also be exploited to separate species during the catching process. We investigated if either positive or negative phototaxis can be used to improve fish vert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 31 publications
1
31
0
Order By: Relevance
“…Consequently, the use of artificial light device with such specific wavelength(s) could play key role essentially to mitigate the catch of such fish juveniles. Recent workers (Hannah et al 2015, Larsen et al 2017, Melli et al 2018) have shown artificial lights as very capable of reducing bycatch during commercial fisheries activities. In this context, it is very pertinent that workers in this specialist endeavour continue to improve their knowledge about behavioural responses of fish species toward artificial light wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, the use of artificial light device with such specific wavelength(s) could play key role essentially to mitigate the catch of such fish juveniles. Recent workers (Hannah et al 2015, Larsen et al 2017, Melli et al 2018) have shown artificial lights as very capable of reducing bycatch during commercial fisheries activities. In this context, it is very pertinent that workers in this specialist endeavour continue to improve their knowledge about behavioural responses of fish species toward artificial light wavelengths.…”
Section: Discussionmentioning
confidence: 99%
“…towing speed) and fishing area. Figure illustrates the BRDs designs: a counter‐herding device (Melli, Karlsen, et al, ), a modification of the upper netting panel in the trawl body (Krag, Herrmann, & Karlsen, ), a horizontally divided trawl codend (Melli, Krag, Herrmann, & Karlsen, , ); a 90 mm diamond mesh codend with a 120 mm square mesh panel (SMP; Krag et al, ); and a 120 mm diamond mesh codend with a 180 mm SMP (Krag, Herrmann, Karlsen, & Mieske, ). Each of these BRDs was effective on at least one of the by‐catch species analysed, without completely excluding all commercial fish from the catch (like a grid would; Frandsen et al, ).…”
Section: Application To a Case‐study Fisherymentioning
confidence: 99%
“…Schematic drawings of the BRDs included in the study. (a) Counter‐herding device from Melli, Karlsen, et al (); (b) large meshes in the upper netting of the trawl body from Krag et al, (); (c) horizontally divided trawl codend from Melli, Krag, et al (); (d) C0: 90 mm diamond codend from Krag et al, (); C1: 120 mm diamond codend from Krag et al, (); C2: 90 mm diamond codend with 120 mm SMP from Krag et al, (); C3: 120 mm diamond codend with 180 mm SMP from Krag et al, ()…”
Section: Application To a Case‐study Fisherymentioning
confidence: 99%
See 1 more Smart Citation
“…However, several studies in the literature have documented that haddock of different sizes may exhibit different behaviour in a trawl (Grimaldo et al, 2018;Melli et al 2017Melli et al , 2018. Therefore, it is relevant to investigate if a modelling approach that avoids the assumption of length independency on the behavioural aspect can improve the modelling of size selectivity processes for haddock in relation to grids and square mesh panels in trawls.…”
Section: R a F Tmentioning
confidence: 99%